The Differential Expression of MicroRNAs Between Implantation Sites and Interimplantation Sites in Early Pregnancy in Mice and Their Potential Functions. (October 2014) - Geng, Yanqing; He, Junlin; Ding, Yubin; Chen, Xuemei; Zhou, Yongjiang; Liu, Shangjing; Liu, Xueqing; Wang, Yingxiong
Embryo implantation is a complex process that involves synchronized crosstalk between a receptive endometrium and a functional blastocyst. It can take place only during the window of implantation, a period when a series of changes in gene expression occur in the endometrium to accept the embryo. As modulators of gene expression, microRNAs (miRNAs) have been identified as regulators of embryo implantation. To better understand how miRNAs regulate implantation and the related molecular mechanisms, we compared the expression profiles of miRNAs and messenger RNAs between implantation sites (IMs) and inter-IMs in the endometrium of pregnant mice on day 5 by microarrays. The results showed that compared with inter-IMs, 30 miRNAs were upregulated and 42 miRNAs (>2-fold) were downregulated at the IMs. By combining the results of the microarray experiments, we found that 20 upregulated pathways and 14 downregulated pathways might be subject to miRNA regulation at IMs. We also found that some miRNAs and their targets may play a key role in implantation.